2016
DOI: 10.3390/nu8110697
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Added Sugars Consumption and Chronic Disease Risk Factors: Current Understanding

Abstract: Added sugars are a controversial and hotly debated topic. Consumption of added sugars has been implicated in increased risk of a variety of chronic diseases including obesity, cardiovascular disease, diabetes and non-alcoholic fatty liver disease (NAFLD) as well as cognitive decline and even some cancers. Support for these putative associations has been challenged, however, on a variety of fronts. The purpose of the current review is to summarize high impact evidence including systematic reviews, meta-analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
120
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 172 publications
(127 citation statements)
references
References 130 publications
(172 reference statements)
0
120
1
6
Order By: Relevance
“…Similarly, using data from the National Health and Nutrition Examination Survey, Hert et al reported that the consumption of sugar-sweetened beverages was associated with the presence of biomarkers for chronic disease risk, independently of demographic and lifestyle factors [10]. Additionally, the consumption of added sugars has been associated with an increased risk of dyslipidaemia [13,28,29] and Welsh et al reported a statistically significant correlation between dietary added sugars and dyslipidaemia among US adults [28]. Interestingly, the lack of association between dietary proteins and fats support the significance of free sugars compared to other nutrients in the disease activity of SLE patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, using data from the National Health and Nutrition Examination Survey, Hert et al reported that the consumption of sugar-sweetened beverages was associated with the presence of biomarkers for chronic disease risk, independently of demographic and lifestyle factors [10]. Additionally, the consumption of added sugars has been associated with an increased risk of dyslipidaemia [13,28,29] and Welsh et al reported a statistically significant correlation between dietary added sugars and dyslipidaemia among US adults [28]. Interestingly, the lack of association between dietary proteins and fats support the significance of free sugars compared to other nutrients in the disease activity of SLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…O'Connor et al reported that higher intakes of free sugar was positively linked to some inflammation markers in a population-based study of adults [12]. Similarly, the excessive consumption of free sugars has been implicated in the increased risk of various diseases characterised by the presence of chronic low-grade inflammation, including obesity, diabetes, and metabolic syndrome [13]. Nevertheless, the potential role of the consumption of free sugar in autoimmune diseases has not yet been examined.…”
Section: Introductionmentioning
confidence: 99%
“…There are loose links between cognitive decline and sugar intake, although there is a sense that cognition more broadly is associated with a healthy diet. [ 7,15,16 ] Ginieis et al., [ 17 ] however, have indicated that “neuro‐cognitive research has confirmed that glucose, as a main energy substrate for the brain, can momentarily benefit cognitive performances, particularly for memory functioning.” This is not surprising in that glucose (which may be derived from relevant disaccharides and starches of course) is the key source of energy for the brain. [ 9,13,18 ] The brain requires a constant drip‐feeding of glucose from the diet.…”
Section: Effects On Healthmentioning
confidence: 99%
“…There appears to be a positive correlation between blood triglyceride (TG), very‐low‐density lipoprotein (VLDL), and low‐density lipoprotein (LDL) and sugar consumption (especially fructose), inversely with high‐density lipoprotein (HDL), as discussed elsewhere. [ 7,16,19,28–30 ] (See also the blood lipid discussion section above.) The blood lipid profile as a consequence of excess sugar consumption is thus a real risk factor and concern for the development of cardiovascular disease.…”
Section: Effects On Healthmentioning
confidence: 99%
See 1 more Smart Citation